Methods of Model Predictive Control for Discrete Multi-Variable Systems with Input - Mishchenko, M.D.; Gubarev, V.F. (Cybernetics and computer engineering, 2020)
A new class of methods capable of leading linear system’s state to zero (or, in case of noisy environment, to its neighbourhood) and stabilization of cognitive map’s functioning was developed. These new methods are capable of controlling not only stable systems, but also unstable and semi-stable ones, even in presence of random perturbations and with constrained control resource. These methods differ in efficiency of control resource utilization and required computational resources. More efficient methods require more computations. That’s why it is necessary to choose an appropriate method in each particular case. Отримано новий клас методів, здатних приводити стан лінійної системи до нуля (або у випадку наявності збурень — до його околу) та стабілізувати функціонування когнітивної карти за скінченний час. Отримані методи можуть керувати не тільки строго стійкими системами, а також і напівстійкими та нестійкими, зокрема і в умовах наявності випадкових збурень та з урахуванням обмеженості ресурсу керування. Розроблені методи різняться за ефективністю використання ресурсу керування та необхідними обчислювальними ресурсами. Ефективніші методи потребують більше обчислень для отримання результату. Це призводить до необхідності вибирати оптимальний метод у кожному конкретному випадку окремо. Был получен новый класс методов, способных приводить состояние линейной системы к нулю (или, в случае присутствия возмущений, к его окрестности) и стабилизировать функционирование когнитивных карт за конечное время. Полученные методы способны управлять не только строго устойчивыми системами, но и системами на грани устойчивости и неустойчивости, в том числе и в условиях присутствия случайных возмущений и с учетом ограниченности ресурса управления. Разработанные методы различаются эффективностью использования ресурса управления и необходимыми вычислительными ресурсами. Более эффективные методы требуют большего количества вычислений для получения результата. Это приводит к необходимости в каждом конкретном случае выбирать свой наиболее оптимальный метод.